ANALISIS PENGUKURAN KINERJA OPERASIONAL RUMAH SAKIT BAKTI TIMAH PANGKALPINANG DENGAN PENDEKATAN BALANCED SCORECARD - Medinal Medinal (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
This study is aim to analyze of Operational Performance Measurement using Balanced Scorecard method. Subject of this research is RSBT Pangkalpinang. This balanced scorecard is a tool that showed the hospital performance based on four perspectives namely financial, customer, internal business process, and learning and growth perspective. This research uses a quantitative-descriptive method. This study using primary and secondary data from 2018-2020. Primary data collection techniques through the distribution of questionnaires and interviews with respondents. The results of the analysis prove that the overall operational performance assessment at the RSBT Pangkalpinang uses a balanced score card that is satisfying and has a good performance mesurement.